2018
DOI: 10.1002/asi.24037
|View full text |Cite
|
Sign up to set email alerts
|

Isolated, overwhelmed, and worried: Young first‐time mothers asking for information and support online

Abstract: This study investigates the emotional content of 174 posts from 162 posters to online forums made by young (age 14-21) first time mothers to understand what emotions are expressed in these posts and how these emotions interact with the types of posts and the indicators of Information Poverty within the posts. Using textual analyses we provide a classification of emotions within posts across three main themes of interaction emotions, response emotions and preoccupation emotions and show that many requests for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
3
43
0
1
Order By: Relevance
“…Both viewpoints are supported by literature, e.g. [41], and both may be factors at this early stage of information need development: problematic situations that give rise to negative emotions states compel us to find solutions [24,25,59], but the negative emotional states may make it difficult for us to think about what information we need.…”
Section: Information Needs Theorymentioning
confidence: 85%
See 1 more Smart Citation
“…Both viewpoints are supported by literature, e.g. [41], and both may be factors at this early stage of information need development: problematic situations that give rise to negative emotions states compel us to find solutions [24,25,59], but the negative emotional states may make it difficult for us to think about what information we need.…”
Section: Information Needs Theorymentioning
confidence: 85%
“…As noted above, with forum posts we cannot clarify with the original poster their intention of posting to a forum. Rather, we can only estimate the most likely reasons for their posting from the text and from any available responses to the post: are they seeking information, are they making an announcement of their situation or simply emotionally 'venting' [41].…”
Section: Datamentioning
confidence: 99%
“…Through a content analysis of breastfeeding concerns and questions expressed on http://Babycenter.com's Breastfeeding Support and Help online community boards, we were able to evaluate the kinds of questions mothers posted and the content and process they used to respond. This study is particularly innovative because although many have examined mother's online information seeking (Bernhardt & Felter, ; Jang et al, ; Porter & Ispa, ; Ruthven, Buchanan, & Jardine, ), none have examined how women seek and respond to breastfeeding information via online discussion forums. Our results demonstrate that women on an online breastfeeding forum are seeking logistical information related to the how‐tos of breastfeeding from other mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasised the utilisation of online parenting forums across all facets of child rearing (Appleton, Fowler, & Brown, ; Milne, Weijs, Haines‐Saah, & McLaren, ; Pedersen & Lupton, ; Ruthven et al, ). Although some researchers have found that the dialogue on these virtual spaces can be contentious (Appleton et al, ), the majority note that they provide a positive means for mothers to express themselves and find the social support they are seeking (Cowie et al, ; Niela‐Vilén et al, ; Pedersen & Lupton, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors identifies that the patients having age less than forty expressed more positive and negative emotions as compared to other age group patients together with that they also analyzed the behavior of partners of these patients and revealed that they expressed more negative emotions as compared to patients. The author proposed novel ensemble machine and deep learning algorithmic approach based on the clustering, classification association rules and NLP on crowd-sourced contents of discussion board (Ruthven, Buchanan, & Jardine, 2018).…”
mentioning
confidence: 99%